2012
DOI: 10.1021/ja304181q
|View full text |Cite
|
Sign up to set email alerts
|

Interference of the Surface of the Solid on the Performance of Tethered Molecular Catalysts

Abstract: The catalytic performance of cinchonidine in the promotion of thiol additions to conjugated ketones was used as a probe to assess the tethering of molecular functionality onto solid surfaces using well-known "click" chemistry involving easy-to-react linkers. It has been assumed in many applications that the tethered molecules retain their chemical properties and dominate the chemistry of the resulting solid systems, but it is shown here that this is not always the case. Indeed, a loss of enantioselectivity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 35 publications
1
42
0
Order By: Relevance
“…As a result of the pore size decrease and of the higher density, a decrease of the specific surface area and pore volumes is observed. This passivation strategy is generally used to inhibit hydrogen bonding activation of the substrate by the silica surface, 90,91 but it is also believed to facilitate the diffusion of organic species, particularly in very polar environments, through enhanced hydrophobicity of the materials. 92 Amine-grafted silicas are being intensively studied as heterogeneous catalysts for Henry and aldol reactions.…”
Section: Towards Multi-functional Materialsmentioning
confidence: 99%
“…As a result of the pore size decrease and of the higher density, a decrease of the specific surface area and pore volumes is observed. This passivation strategy is generally used to inhibit hydrogen bonding activation of the substrate by the silica surface, 90,91 but it is also believed to facilitate the diffusion of organic species, particularly in very polar environments, through enhanced hydrophobicity of the materials. 92 Amine-grafted silicas are being intensively studied as heterogeneous catalysts for Henry and aldol reactions.…”
Section: Towards Multi-functional Materialsmentioning
confidence: 99%
“…[250] Because of their larger pore sizes, ordered mesoporous materials can be used to overcome the constraints of zeolites and to allow more facile diffusion of bulky substrates, but they also offer less promise as agents to control catalytic selectivity on the basis of pore size and shape. [18,[255][256][257] In most cases, the added selectivity originates from the particular chemical properties of the added molecules, but it is also possible, in principle, to use tethered molecules to partially block the inside volume of the pores in a specific manner to create a sculpted space for the active catalytic site. [24,251] Tethering of molecular functional groups to the surfaces of SiO 2 has been developed extensively in recent years.…”
Section: Postmodification Of Pores and The Encapsulation Of The Activmentioning
confidence: 99%
“…[252][253][254] Enantioselectivity can be added in this way as well by tethering chiral compounds. [18,[255][256][257] In most cases, the added selectivity originates from the particular chemical properties of the added molecules, but it is also possible, in principle, to use tethered molecules to partially block the inside volume of the pores in a specific manner to create a sculpted space for the active catalytic site. To the best of our knowledge, this has not yet been attempted.…”
Section: Postmodification Of Pores and The Encapsulation Of The Activmentioning
confidence: 99%
“…One way to address this problem is to employ solid supports for the immobilization of homogeneous catalysts . The selection of support is critical, as it affects catalytic efficiency …”
Section: Introductionmentioning
confidence: 99%
“…[3,4] The selection of support is critical, as it affects catalytic efficiency. [5][6][7][8] Recent studies have indicated that magnetite nanoparticles with superparamagnetic behaviour are appropriate supports for immobilizing catalysts and may facilitate isolation of catalysts from reaction mixtures with an external magnetic field. Functionalization of the surface of magnetite nanoparticles is a well-known method for the preparation of magnetically recyclable heterogeneous catalysts.…”
mentioning
confidence: 99%